Injectable, Magnetically Orienting Electrospun Fiber Conduits for Neuron Guidance - Johnson, Christopher D. L. (ACS Appl Mater Interfaces, 2018)
Magnetic electrospun fibers are of interest for minimally invasive biomaterial applications that also strive to provide cell guidance. Magnetic electrospun fibers can be injected and then magnetically positioned in situ, and the aligned fiber scaffolds provide consistent topographical guidance to cells. In this study, magnetically responsive aligned poly-L-lactic acid electrospun fiber scaffolds were developed and tested for neural applications. Incorporating oleic acid-coated iron oxide nanoparticles significantly increased neurite outgrowth, reduced the fiber alignment, and increased the surface nanotopography of the electrospun fibers. After verifying neuron viability on two-dimensional scaffolds, the system was tested as an injectable three-dimensional scaffold. Small conduits of aligned magnetic fibers were easily injected in a collagen or fibrinogen hydrogel solution and repositioned using an external magnetic field. The aligned magnetic fibers provided internal directional guidance to neurites within a three-dimensional collagen or fibrin model hydrogel, supplemented with Matrigel. Neurites growing from dorsal root ganglion explants extended 1.4–3× farther on the aligned fibers compared with neurites extending in the hydrogel alone. Overall, these results show that magnetic electrospun fiber scaffolds can be injected and manipulated with a magnetic field in situ to provide directional guidance to neurons inside an injectable hydrogel. Most importantly, this injectable guidance system increased both neurite alignment and neurite length within the hydrogel scaffold.